Interscalene Brachial Plexus Block with Liposomal Bupivacaine versus Standard Bupivacaine with Perineural Dexamethasone: A Noninferiority Trial. (18th January 2022) - Kim, David H.; Liu, Jiabin; Beathe, Jonathan C.; Lin, Yi; Wetmore, Douglas S.; Kim, Sang J.; Haskins, Stephen C.; Garvin, Sean; Oxendine, Joseph A.; Ho, Michael C.; Allen, Answorth A.; Popovic, Marko; et al.
Abstract : Background: The interscalene nerve block provides analgesia for shoulder surgery. To extend block duration, provide adequate analgesia, and minimize opioid consumption, the use of adjuvants such as dexamethasone as well as the application of perineural liposomal bupivacaine have been proposed. This randomized, double-blinded, noninferiority trial hypothesized that perineural liposomal bupivacaine is noninferior to standard bupivacaine with perineural dexamethasone in respect to average pain scores in the first 72 h after surgery. Methods: A total of 112 patients undergoing ambulatory shoulder surgery were randomized into two groups. The liposomal bupivacaine group received a 15-ml premixed admixture of 10 ml of 133 mg liposomal bupivacaine and 5 ml of 0.5% bupivacaine (n = 55), while the bupivacaine with dexamethasone group received an admixture of 15 ml of 0.5% standard bupivacaine with 4 mg dexamethasone (n = 56), respectively. The primary outcome was the average numerical rating scale pain scores at rest over 72 h. The mean difference between the two groups was compared against a noninferiority margin of 1.3. Secondary outcomes were analgesic block duration, motor and sensory resolution, opioid consumption, numerical rating scale pain scores at rest and movement on postoperative days 1 to 4 and again on postoperative day 7, patient satisfaction, readiness for postanesthesia care unit discharge, and adverse events. Results: A liposomal bupivacaine group average numerical rating scale pain score over 72 h was not inferior to the bupivacaine with dexamethasone group (mean [SD], 2.4 [1.9] vs. 3.4 [1.9]; mean difference [95% CI], –1.1 [–1.8, –0.4]; P < 0.001 for noninferiority). There was no significant difference in duration of analgesia between the groups (26 [20, 42] h vs. 27 [20, 39] h; P = 0.851). Motor and sensory resolutions were similar in both groups: 27 (21, 48) h versus 27 (19, 40) h ( P = 0.436) and 27 [21, 44] h versus 31 (20, 42) h ( P = 0.862), respectively. There was no difference in opioid consumption, readiness for postanesthesia care unit discharge, or adverse events. Conclusions: Interscalene nerve blocks with perineural liposomal bupivacaine provided effective analgesia similar to the perineural standard bupivacaine with dexamethasone. The results show that bupivacaine with dexamethasone can be used interchangeably with liposomal bupivacaine for analgesia after shoulder surgery. Abstract : Interscalene nerve blocks using bupivacaine plus dexamethasone were compared with blocks using liposomal bupivacaine for shoulder surgery. These alternative blocks provided very similar levels and durations of analgesia, and no differences in opioid consumption were identified. The interscalene injection of bupivacaine plus dexamethasone and liposomal bupivacaine provide similar clinical benefits for shoulder surgery.